(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Mental health refers to the emotional, psychological and social well-being of an individual, and it is just as important as physical health. Mental health care and its management have become increasingly important in contemporary times. With the prevalence of mental health disorders on the rise, it is crucial that individuals receive adequate support and treatment to manage their mental health.